EVALUASI KEGAGALAN START UP BISNIS: (STUDI KASUS DI LAHAP) - William Henadad Laluyan; Liliana Dewi (STIE Mahardhika, 2020)
Lahap is a small and medium enterprise that runs engaged in food and beverage field that began to established since 2016. The type of product offered is abon. Lahap produces abon cakalang that has its own uniqueness because the abon cakalang is not available in Surabaya Lahap fish to replace with deho fish. For 12 months the sale target has never been achieved that become a negative thing for Lahap company. The purpose of this research was to evaluate the factors that cause the failure of Lahap business. The determination of data sources on the subject is determined by certain considerations, facilitators, and expert lecturers who have got experience in the food and beverage field. The method that is used is the descriptive qualitative method by using a semi-structured interview method. Then the data is tested by using validity and reliability test. The results of the research show that less competent in managerial, experience from the owner, motivation from the owner, planning that is done and resources that cause the company failed.